Rationality applied: resolving the two envelopes problem - Christian Hugo Hoffmann (Theory and Decision, 2022)
The Two Envelopes Problem is a beautiful and quite confusing problem in decision theory which is ca. 35~years old and has provoked at least 150 papers directly addressing the problem and displaying a surprising variety of different responses. This paper finds decisive progress in an approach of Priest and Restall in 2003, contends that the recent papers having appeared since did not really go beyond that paper, argues further that Priest's and Restall's solution is still not complete, and proposes a completion of their solution. If the analysis is correct, this work has the potential of laying the Two Envelopes Problem at rest.
Keywords: 300; Two envelopes problem; Decision theory; Paradox; Probability; Methodology